PENINGKATAN HASIL BELAJAR IPA SISWA MELALUIMODEL PEMBELAJARAN CTL (CONTEXTUAL THEACING AND LEARNING)DI KELAS V A SDN 021 TANJUNG PALAS - Jenny (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low science learning outcomes of fifth-grade students at SDN 021 Tanjung Palas, where out of 25 students only 8 students (32.00%) achieved learning mastery. The low learning outcomes were caused by several factors, including: (a) students’ lack of enthusiasm for learning; (b) students’ inability to answer reasoning-based questions; (c) limited student involvement in the learning process; (d) suboptimal use of learning media or teaching aids; and (e) students’ low level of understanding of science subject matter. This research was conducted as a classroom action research (PTK) aimed at describing learning outcomes through the use of the Contextual Teaching and Learning (CTL) model. The subjects of this study were students of class V A at SDN 021 Tanjung Palas, and the research was carried out in two cycles. Improvements in learning outcomes were analyzed based on four categories, namely learning absorption, learning effectiveness, mastery learning completeness at both individual and classical levels, and overall learning achievement. Data were collected using oral tests and written tests in the form of worksheets administered after the learning process. The results showed that students’ science learning outcomes improved in each cycle, as indicated by mastery learning achievement, where in the first cycle 15 students (60%) achieved mastery and in the second cycle the number increased to 22 students (88%). It can be concluded that the application of the CTL learning model can improve science learning outcomes of fifth-grade students at SDN 021 Tanjung Palas.